Removal of Oil and Grease as Emerging Pollutants of Concern (EPC) in Wastewater Stream - Abass O, Alade; Jameel, Ahmad T.; Muyubi, Suleyman A.; Abdul Karim, Mohamad I.; Alam, and Md. Zahangir (IIUM Engineering Journal, 2011)
Wastewater characteristics, which depend on wastewater source, are increasingly becoming more toxic in recent times. The concentrations of oil and grease in wastewater streams have been observed to increase in wastewater stream with increasing adverse effects on the ecology. This results from the increasing use of oil and grease in high-demanded oil-processed foods, establishment and expansion of oil mills and refineries worldwide, as well as indiscriminate discharge of oil and grease into the water drains, domestically and industrially. This study reports the applications, efficiencies and challenges of the wastewater treatment techniques currently employed in the removal of oil and grease from the industrial wastewater and municipal water stream. The results shows that the concentrations of oil and grease injected into the ecosystem are of higher environmental impact and this needs to be given the desired attention. The desired development for effective removal of oil and grease as emerging pollutants of concern (EPC) in wastewater stream are thus proposed. ABSTRAK: Ciri-ciri air sisa, bergantung kepada punca air sisa tersebut, menjadi semakin toksik akhir-akhir ini. Kepekatan minyak dan gris dalam air sisa anak sungai dilihat makin bertambah dalam air sisa anak sungai dengan bertambahnya kesan negatif ke atas ekologi. Ini disebabkan oleh peningkatan penggunaan minyak dan gris dalam makanan berproses yang tinggi permintaannya, penubuhan dan perkembangan kilang pertroleum dan loji penapisan di seluruh dunia. Minyak dan gris juga dibuang sewenang-wenangnya ke dalam parit air, dari kalangan domestik dan industry. Kajian ini membentangkan tentang aplikasi, keberkesanan dan teknik cabaran rawatan air buangan yang kini digunakan dalam pembuangan minyak dan gris dari air sisa industry dan air sungai perbandaran. Keputusan menunjukkan kepekatan minyak dan gris yang wujud dibuang ke dalam ekosistem mempunyai impak yang lebih tinggi terhadap persekitaran dan hal ini perlu diambil berat. Keinginan untuk kemajuan penyingkiran minyak dan gris sebagai keprihatinan terhadap pencemaran (emerging pollutants of concern (EPC))ke atas air sisa sungai dicadangkan. Key words: wastewater, oil and grease, emerging pollutant of concern